Control activities and compliance behavior: survey evidence from Norway - Diekert, Florian; Nøstbakken, Linda; Richter, Andries (Marine policy, 2021)
Successful fisheries management relies on compliance. Compliance in turn relies on the perceived legitimacy of the existing rules and regulations, the effectiveness of monitoring and enforcement, and on the positive feedback loop between legitimacy and effectiveness. Against the backdrop of increasing incentives to violate rules and regulations in modern fisheries, there are concerns that traditional control activities relying on physical in spections, are no longer effective in safeguarding sustainability. Modern control activities, which make use of new technologies, such as camera surveillance on vessels, remote monitoring (drones, planes, satellites) and realtime monitoring of catches with automated data recording, may offer a promising alternative to enforcement officers conducting physical inspections. This paper presents evidence from a large-scale survey among Nor wegian fishers, investigating (i) attitudes towards traditional and modern control activities, and (ii) how ex pectations about and experiences of physical inspections affect compliance behavior. We also investigate the role of individual factors on compliance, such as risk aversion, which we measure with an economic experiment. While we cannot document an effect of risk aversion on compliance behavior, we find that having experienced more controls in the past and perceiving the likelihood of future control as higher, significantly reduce rule violations. We also find that survey respondents appreciate traditional enforcement measures, while they have mixed attitudes towards modern control activities.